The correct answer for this very hard equation would happen to be 12 because 18+12 happens to equal 30 and 42-30 just so happens to equal 12
Subtract 3 first so it would be 7x=15
then divide by 7 so x would be approximately 2.14
Answer:
Step-by-step explanation:
Simplifying
3.4 + 2(9.7 + -4.8x) = 61.2
3.4 + (9.7 * 2 + -4.8x * 2) = 61.2
3.4 + (19.4 + -9.6x) = 61.2
Combine like terms: 3.4 + 19.4 = 22.8
22.8 + -9.6x = 61.2
Solving
22.8 + -9.6x = 61.2
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-22.8' to each side of the equation.
22.8 + -22.8 + -9.6x = 61.2 + -22.8
Combine like terms: 22.8 + -22.8 = 0.0
0.0 + -9.6x = 61.2 + -22.8
-9.6x = 61.2 + -22.8
Combine like terms: 61.2 + -22.8 = 38.4
-9.6x = 38.4
Divide each side by '-9.6'.
x = -4
Simplifying
x = -4
Step-by-step explanation:
y'=dy/dx=d/dx(4x³+3x²-2x+9)
=(3*4x^(3-1)+2*3x^(2-1)-2*1x^(1-1)+9*0
y'=12x²+6x-2